NOX2 Inhibition Impairs Early Muscle Gene Expression Induced by a Single Exercise Bout - Henríquez-Olguín, Carlos; Díaz-Vegas, Alexis; Utreras-Mendoza, Yildy; Campos, Cristian; Arias-Calderón, Manuel; Llanos, Paola; Contreras-Ferrat, Ariel; Espinosa, Alejandra; Altamirano, Francisco; Jaimovich, Enrique; Valladares, Denisse M. (Frontiers in Physiology, 2016)
Reactive oxygen species (ROS) participate as signaling molecules in response to exercise in skeletal muscle. However, the source of ROS and the molecular mechanisms involved in these phenomena are still not completely understood. The aim of this work was to study the role of skeletal muscle NADPH oxidase isoform 2 (NOX2) in the molecular response to physical exercise in skeletal muscle. BALB/c mice, pre-treated with a NOX2 inhibitor, apocynin, (3 mg/kg) or vehicle for 3 days, were swim-exercised for 60 min. Phospho-p47phox levels were significantly upregulated by exercise in flexor digitorum brevis (FDB). Moreover, exercise significantly increased NOX2 complex assembly (p47phox-gp91phox interaction) demonstrated by both proximity ligation assay and co-immunoprecipitation. Exercise-induced NOX2 activation was completely inhibited by apocynin treatment. As expected, exercise increased the mRNA levels of manganese superoxide dismutase (MnSOD), glutathione peroxidase (GPx), citrate synthase (CS), mitochondrial transcription factor A (tfam) and interleukin-6 (IL-6) in FDB muscles. Moreover, the apocynin treatment was associated to a reduced activation of p38 MAP kinase, ERK 1/2, and NF-κB signaling pathways after a single bout of exercise. Additionally, the increase in plasma IL-6 elicited by exercise was decreased in apocynin-treated mice compared with the exercised vehicle-group (p<0.001). These results were corroborated using gp91-dstat in an in-vitro exercise model. In conclusion, NOX2 inhibition by both apocynin and gp91dstat, alters the intracellular signaling to exercise and electrical stimuli in skeletal muscle, suggesting that NOX2 plays a critical role in molecular response to an acute exercise.